The link between high tech export intensity and telecommunications infrastructure - Alinsunurin, Jason P. (Animo Repository, 2014)
This paper aims to explain the link between economies’ high-technology export intensity and telecommunications infrastructure. Using panel data from the World Development Indicators, our generalized least squares estimates show telephone, internet and mobile phone densities to have strong, positive and statistically significant impacts to the share of high tech export shares to total exports. The impact of telephone density is the strongest, with a 0.23 percentage point increase in the share of the high tech for every additional telephone made available to every 100 persons. Internet and mobile phone densities of up to 35.23 and 54.16 per 100 persons respectively show strong impacts, but display diminishing marginal effects beyond optimal density ratios. The paper underscores the importance of telecommunication infrastructures in the growth of high technology intensive sectors, most especially among developing countries.